Berj Fazlian՚s “Othello” on the Armenian Stage in Canada - Bekaryan, Anahit (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
From the beginning of their settlement in Canada, since the early 1900s, Armenians have been actively engaged in organizing and holding modest shows and gatherings with recitals, songs, theatrical rehearsals, and impromptu performances. Their purpose was to unite the Armenians of the community, as well as to raise funds in favour of Armenian immigrants, schools, and hospitals. Although the performances of those shows and gatherings did not have any outstanding artistic value, it is an undeniable fact that they played a significant role in educating the younger generation of Armenians in the spirit of national-cultural traditions, preserving national identity, and served their main goal of uniting the Armenians of Canada to acquaint and connect them with the national theatre. In this regard, the organizers of the aforementioned events deserve all the praise and high evaluation. 1976-ին թատերական գործիչ, դերասան, բեմադրիչ Պերճ Ֆազլյանը (1926-2016) հիմնեց Մոնրեալի Թեքեյան մշակութային միության «Հայ բեմ» թատերախումբը, որը կանադահայ թատերական կյանքին հաղորդեց բարձր որակ ու նոր մակարդակ: 1984 թ. փետրվարին թատերախմբի ուժերով Կանադայում առաջին անգամ հայերենով բեմադրվեց Շեքսպիրի «Օթելլոն», որն ունեցավ մեծ հաջողություն ինչպես հայ, այնպես էլ օտար հասարակության շրջանում: Մամուլից քաղված տեղեկությունները վկայում են Պերճ Ֆազլյանի և սիրող դերասանների բարձր պրոֆեսիոնալիզմի մասին: Կանադայի և ԱՄՆ-ի հայաշատ քաղաքներից ստացած հրավերները ևս հաստատում են, որ ներկայացումը ունեցել է մեծ հաջողություն: В 1976 году известный армянский театральный деятель Перч Фазлян (1926-2016) основал в Монреале армянскую театральную труппу «Ай бем» (Ар-мянская сцена) культурного общества Текеян. Силами этой труппы в феврале 1984 года впервые в Канаде на армянском языке была поставлена трагедия Шекспира «Отелло». Спектакль имел огромный успех как у армянских, так и иностранных зрителей. Канадская периодика отметила высокий профессиональный уровень П. Фазляна и актеров-любителей. Труппа получала приглашения из разных армянонаселенных городов Канады и США, и везде спектакль шел с неизменным успехом.
Keywords: Theater; Film Studies; Dramaturgy